How can food system actors influence food system resilience? A literature review via an actor-based lens - Jing Zhang; David Tyfield; Lingxuan Liu (Environmental Research: Food Systems)
A growing body of research highlights the central role that actors play in shaping food system resilience. While individual studies have examined the contributions of specific actors, there remains a lack of synthesis that captures cross-sectoral patterns and underlying mechanisms. This review addresses this gap by analysing empirical evidence on how food system actors influencing food system resilience in the face of disruptions—not through abstract system properties alone, but through their concrete activities, capacities, and relationships. Drawing on studies that focus on producers, intermediaries in the supply chain, and consumers, this review identifies four recurring mechanisms through which actors influence food system resilience: (1) actors’ capability and agency to act under pressure; (2) the diversity of actors and their functions; (3) the connectivity and connections among actors; and (4) actors’ capacity to learn and adapt. These mechanisms underpin the system’s ability to sustain or reconfigure essential functions during crises. In addition, the review highlights the importance of supportive structures that bind actors to one another and to the broader food system. These include physical and institutional infrastructures such as logistics, energy, natural resources, digital platforms, and governance systems. Actor influence is also shaped by geographic location and position within the value chain, which affect their access to resources and ability to respond. Recognising that actors’ interests may not always align with system-level resilience, it is imperative to critically explore whose resilience is being supported, and for governance approaches that foster collective, system-oriented agency.